Principles of Textual Rhetoric in CakCuk Discourse - Foriyani Subiyatningsih (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
This research aims to study how the creator of CakCuk creates language based on the principles and maxims of textual rhetoric in CakCuk designs. The data was collected using a method of observation, with a basic technique of recording followed by a technique of note-taking. The data analysis used a method of distribution, comparison, and contextual identity. The results of this study show that CakCuk discourse is a product of the language creativity of its creator through the utilization of principles or maxims of textual rhetoric. The key to this creativity is the creator’s ability to use maxims in order to achieve efficiency, clarity, effectiveness, and attractiveness in the text. The motivation underlying the choice of principles/maxims is: (i) the principle of processability in order to determine the main focus and weighting of the text; (ii) the principle of clarity in order to make the message clear; (iii) the principle of economy in order to keep the text as short as possible; (iv) the principle of expressiveness in order to make the text effective.